2006
DOI: 10.1007/s00787-006-1010-0
|View full text |Cite
|
Sign up to set email alerts
|

The Family Strain Index (FSI). Reliability, validity, and factor structure of a brief questionnaire for families of children with ADHD

Abstract: The ease of completion and coherence of the underlying construct indicates that the FSI may be a practical clinical tool for monitoring changes in family strain associated with children's ADHD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 24 publications
4
39
1
Order By: Relevance
“…In the ADORE study, 73% of parents reported that their child/ adolescent with ADHD caused conflict or tension within the family at least sometimes, and 73% also reported limited time to relax or participate in social activities (Riley et al, 2006b). Our findings are generally in line with these data.…”
Section: Characteristicsupporting
confidence: 89%
“…In the ADORE study, 73% of parents reported that their child/ adolescent with ADHD caused conflict or tension within the family at least sometimes, and 73% also reported limited time to relax or participate in social activities (Riley et al, 2006b). Our findings are generally in line with these data.…”
Section: Characteristicsupporting
confidence: 89%
“…Numerous studies (e.g., Anastopoulos et al 1992;Breen and Barkley 1988;Harrison and Sofronoff 2002;Mash and Johnston 1983;Podolski and Nigg 2001;Riley et al 2006;van der Oord et al 2006), have reported elevated and clinical rates of parenting stress as a function of child ADHD symptoms. These studies have identified child-level predictors of increased parenting stress in families of children with ADHD, including internalizing (Beck et al 1990; Breen and Barkley 1988;Mash and Johnston 1983) and externalizing behaviours (e.g., Anastopoulos et al 1992;Podolski and Nigg 2001;van der Oord et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The questionnaire was completed by parents from a total of 1,478 families in 10 European countries. All three of these studies were mainly intended to contribute to the development of satisfactory investigational methods (Riley et al 2006c).…”
Section: Introductionmentioning
confidence: 99%